Adsorption of Sulfonamide Antibiotic onto Activated Carbon Prepared from an Agro-industrial By-Product as Low-Cost Adsorbent: Equilibrium, Thermodynamic, and Kinetic Studies - Aslan, Sibel; Sirazi, Meltem (Springer Int Publ Ag, 2020)
Olive pomace (OP) is an agricultural by-product of the olive oil production process. Olive oil mills generate a huge amount of OP that has adverse impacts on the environment due to its phytotoxic properties. Therefore, the utilization of OP in the production of activated carbon may be considered as an alternative eco-friendly solution for disposal and recycling of this waste. The adsorption of sulfadiazine (SDZ), an antibiotic of the sulfonamide group, using activated carbon from olive pomace (OPAC) was investigated under different experimental conditions. The characterization of synthesized activated carbon samples was performed by elemental analysis, BET surface area, total pore volume, average pore size, pH(pzc), FTIR, and SEM-EDX analysis. In batch experiments, the effects of adsorption parameters such as pH of the solution, contact time, activated carbon dosage, initial SDZ concentration, and temperature were assessed. The results showed that the pH of the solution slightly affected the SDZ adsorption capacity of OPAC. In order to express the adsorption behavior of SDZ onto OPAC, Langmuir, Freundlich, Dubinin-Radushkevich (D-R), and Temkin isotherm models were applied to the experimental equilibrium data. The maximum adsorption capacity calculated from the Langmuir isotherm was 66.2252 mg/g at 298 K. The data from kinetic studies were analyzed using pseudo-first-order and pseudo-second-order models. The results indicated that the adsorption process of SDZ onto OPAC followed the pseudo-second-order model rather than the pseudo-first-order model. Based on the thermodynamic parameters including Delta G(0), increment H-0, and increment S-0, it can be concluded that the nature of the adsorption process is exothermic, spontaneous, and favorable and of increased disorder and randomness. This work demonstrates that OP can be used as a precursor for activated carbon production and may substitute with commercial activated carbon for the removal of antibiotics from aqueous media. The production of activated carbon from OP will provide both minimization and recovery of this waste.
Keywords: Antibiotics; Sulfadiazine (SDZ); Adsorption; Activated carbon; Olive pomace